The structural basis of proton driven zinc transport by ZntB. Issue 1 (December 2017) - Gati, Cornelius; Stetsenko, Artem; Slotboom, Dirk; Scheres, Sjors; Guskov, Albert
Abstract Zinc is an essential microelement to sustain all forms of life. However, excess of zinc is toxic, therefore dedicated import, export and storage proteins for tight regulation of the zinc concentration have evolved. In Enterobacteriaceae, several membrane transporters are involved in zinc homeostasis and linked to virulence. ZntB has been proposed to play a role in the export of zinc, but the transport mechanism of ZntB is poorly understood and based only on experimental characterization of its distant homologue CorA magnesium channel. Here, we report the cryo-electron microscopy structure of full-length ZntB fromEscherichia coli together with the results of isothermal titration calorimetry, and radio-ligand uptake and fluorescent transport assays on ZntB reconstituted into liposomes. Our results show that ZntB mediates Zn2+ uptake, stimulated by a pH gradient across the membrane, using a transport mechanism that does not resemble the one proposed for homologous CorA channels. The bacterial zinc transporter ZntB is important for maintaining zinc homeostasis and is mechanistically not well understood. Here, the authors present the cryo-EM structure of ZntB at 4.2 Å resolution, perform transport assays and propose a model for its Zn2+ transport mechanism.